Belajar Melalui Pengalaman Historis (BMPH) Pada Siswa SMA Muhammadiyah 1 Unismuh Makassar - Asmunandar Asmunandar; Bahri Bahri; Khaeruddin Khaeruddin (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
BMPH stands for Learning Through Historical Experience, which is a paradigm of experience from a historical background that becomes an experience in life that will serve as a source of historical and cultural learning for students of SMA Muhammadiyah 1 Unismuh Makassar. Currently, with the development of globalization, it is very important for students to love culture to instill awareness of the importance of experience through culture, which can be used by students as a learning process to learn from the historical environment of local cultural wisdom in ethnic communities in Makassar City, South Sulawesi Province. Learning Through Historical Experience aims to provide knowledge and understanding of BMPH to students at SMA Muhammadiyah 1 Unismuh Makassar class X and students can practice and have awareness, the importance of preserving historical culture in everyday life. The implementation method is carried out online by introducing cultural heritage sites in Makassar City such as Rotterdam Fort, Cathedral Church, Malay Mosque, Kwan Kong Temple, Societeit de Harmonie, as well as traditional arts and dances, both in the form of explanations, in the form of photos, and videos that are studied as a form of historical culture in the Makassar ethnic community which are important to be inherited through learning.